Jointed LDPC codes design for half-duplex relay channels - Zi-qiang CHEN; Shan OUYANG; Hai-lin XIAO; Yue-lei XIE (Tongxin xuebao)
In order to increase the coding gain of decode-and-forward half-duplex relay channel, a jointed LDPC coding structure and its corresponding optimization scheme was proposed. Novel structure made the subcodes of both source and relay nodes as parts of the overall code. Using the messages from the source and the relay, the destination could decode the information of the source and relay nodes simultaneously. To analyze the asymptotic coding gain of jointed LDPC codes, the iterative decoding convergence condition was derived in AWGN channel. Combining the iterative decoding convergence condition and the degree distribution constraint, the optimization problem of the jointed LDPC code degree distribution was presented. The simulation results show that jointed LDPC codes outperform both BE-LDPC codes and SP codes.